Harmonic elimination of a photo-voltaic based cascaded H-bridge multilevel inverter using PSO (particle swarm optimization) for induction motor drive - Sudha Letha, Shimi; Thakur, Tilak; Kumar, Jagdish (Energy (Oxford), 2016)
The present paper proposes a novel method to eliminate harmonics in a solar powered CHMLI (cascaded H-bridge multilevel inverter). The problem uses Newton Raphson and PSO (Particle Swarm Optimization) based SHE (Selective Harmonic Elimination) techniques for solving the non-linear transcendental equations and to obtain the optimal switching angles. The optimized switching angles obtained offline are utilized to minimize the THD (Total Harmonic Distortion). The major concern in the harmonic-elimination problem in the non-equal dc sources system is the solution of the nonlinear transcendental equations. However, the proposed method can solve this problem in a simpler manner, by just converting non-equal dc sources into equal dc source using the ANFIS (Adaptive Neuro Fuzzy Inference System)/Constant Voltage Maximum Power Point Tracker algorithm for the Photo-voltaic system. The performance are evaluated using simulation results for PV fed 11-level cascade H-bridge inverter with induction motor drive. The simulation results are validated using an experimental model of CHMLI with Xilinx Spartan®-3A DSP FPGA based controller. •Harmonic elimination of solar powered cascaded H-bridge multilevel inverter.•Input dc voltage to CHMLI was made constant using ANFIS/CVT MPPT algorithm.•NR and PSO based SHE algorithm were developed for 11 level CHMLI.•PSO-SHE algorithm minimized THD within the acceptable 5% limit of IEEE 519 standard.•Reduced deadly harmonics 5, 7, 11 and 13 to acceptable 3% limit of IEEE 519 standard.